2016
DOI: 10.1039/c5mt00256g
|View full text |Cite
|
Sign up to set email alerts
|

Mercury-mediated cross-resistance to tellurite in Pseudomonas spp. isolated from the Chilean Antarctic territory

Abstract: Mercury salts and tellurite are among the most toxic compounds for microorganisms on Earth. Bacterial mercury resistance is established mainly via mercury reduction by the mer operon system. However, specific mechanisms underlying tellurite resistance are unknown to date. To identify new mechanisms for tellurite detoxification we demonstrate that mercury resistance mechanisms can trigger cross-protection against tellurite to a group of Pseudomonads isolated from the Chilean Antarctic territory. Sequencing of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 70 publications
2
20
0
Order By: Relevance
“…Bacterium isolation was carried out in LB medium supplemented with increasing concentrations of mercury and tellurite (Rodríguez-Rojas et al, 2015). Briefly, P. putida ATH-43 was grown aerobically in LB medium supplemented with 40 μM HgCl 2 at 25°C for 48 h. DNA extraction was performed using the Wizard® Genomic DNA Purification Kit (Promega).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacterium isolation was carried out in LB medium supplemented with increasing concentrations of mercury and tellurite (Rodríguez-Rojas et al, 2015). Briefly, P. putida ATH-43 was grown aerobically in LB medium supplemented with 40 μM HgCl 2 at 25°C for 48 h. DNA extraction was performed using the Wizard® Genomic DNA Purification Kit (Promega).…”
Section: Methodsmentioning
confidence: 99%
“…Members of P. putida are largely known for their ability to colonize different kinds of environments and to degrade a vast diversity of toxic organic compounds (Wu et al, 2011). In this context, P. putida ATH-43 was isolated from soil sediments at the “Prat” Chilean military base located in Greenwich Island, Antarctica, and was recognized as a mercury/tellurite resistant bacterium (Rodríguez-Rojas et al, 2015). Interestingly, this strain shows tellurite resistance only when grown in the presence of mercury, suggesting a cross-resistance mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GSH and thioredoxins are oxidized or consumed when they reduce and sequester Hg(II) (5,6,26,27), and this interaction with Hg can lead to disulfide stress. Mercury exposure can also produce reactive oxygen species (ROS), such as superoxide and hydrogen peroxide (6,26,27). Therefore, we evaluated the possibility that, in T. thermophilus, the 7.5-min induction of LMW thiol genes was due to these indirect effects triggered by Hg(II).…”
Section: Transcription Of Thiol-related Genes Is Induced By Hg(ii)mentioning
confidence: 99%
“…Studies of extreme, polar environments characterized by a still limited anthropogenic influence (e.g., High Arctic or Antarctica) are of great importance, as they may reveal novel genes encoding heavy metal-resistance and metabolism mechanisms, and show the role of naturally occurring microorganisms in biogeochemical cycles. The results of several studies revealed that bacteria isolated from various Arctic and Antarctic environments show resistances to various toxic, antimicrobial agents, such as antibiotics and heavy metals (De Souza et al 2006Lo Giudice et al 2013;Mangano et al 2014;Moller et al 2014;Tomova et al 2014;Perron et al 2015;Rahman et al 2015;Tomova et al 2015;González-Aravena et al 2016;Rodriguez-Rojas et al 2016). However, overall knowledge on the resistome of polar bacteria is still rather limited, and the lack of a systematic approach, combining chemical, microbiological, and molecular analyses, is apparent.…”
Section: Introductionmentioning
confidence: 99%